Конечно-разностная миграция в трехмерном варианте с распараллеливанием процесса вычислений - Верпаховская, А.О.; Пилипенко, В.Н.; Пилипенко, Е.В. (Геоінформатика, 2016)
Переход сейсморазведки на трехмерные или площадные системы наблюдений ведет к значительному увеличению объема зарегистрированных волновых полей, которые необходимо обработать в кратчайшие сроки. При этом необходимо учитывать постоянно возрастающие требования к детальности результата и сложность строения изучаемой площади. В то же время, несмотря на быстрый прогресс в области развития вычислительной техники, появляется проблема недостаточности ресурсов для обработки трехмерных сейсмических наблюдений на отдельно взятом компьютере. Поэтому задача программной реализации существующих процедур обработки с привлечением кластера становится чрезвычайно актуальной в современной сейсморазведке. Рассмотрены разработанные алгоритм и программная реализация трехмерной конечно-разностной миграции после суммы с распараллеливанием процесса вычислений. Перехід сейсморозвідки на тривимірні або площові системи спостережень приводить до значного збільшення обсягу зареєстрованих хвильових полів, які необхідно обробити у найкоротші терміни. При цьому потрібно враховувати постійно зростаючі вимоги до детальності результату і складність будови досліджуваної площі. Водночас, незважаючи на швидкий прогрес у сфері розвитку обчислювальної техніки, з’являється проблема недостатності ресурсів для обробки тривимірних сейсмічних спостережень на окремо взятому комп’ютері. Тому задача програмної реалізації існуючих процедур обробки із залученням кластера стає надзвичайно актуальною в сучасній сейсморозвідці. Розглянуто розроблені алгоритм і програмну реалізацію тривимірної скінченнорізницевої міграції після суми з розпаралелюванням процесу обчислень. The purpose of the paper is to develop a three-dimensional post stack finite-difference migration with parallelization of computing process to process 3D seismic observations on a separate computer, taking into account the ever-increasing requirements for detailed results and the complexity of the structure of the study area. The effectiveness of the developed version of the post stack finite-difference migration is proved with practical examples, in particular, for the structure of medium complicated by the presence of the salt body.
Design/methodology/approach. Algorithm of a three-dimensional post stack migration is based on reverse full-wave field continuation in the medium that is carried out by solving the differential wave equation using a finite difference method. In this case the differential wave equation is approximated by the difference one in the four-dimensional space-time grid. In this approach, the coordinate system is converted according to the seismic wave propagation from the depths to the surface, ensuring optimal finite-difference wave field continuation. Parallelization of computations process is on time slices which are defined with a queue. The calculation of the previous slice is stored in the intermediate memory cube. In parallelizing we used library pthread, which is present in all modern versions of the Linux system and allows you to control the execution of the task in the separation calculations on several processors. The software was developed according to the proposed algorithm of a three-dimensional post stack finite-difference migration with parallelization of the computing process for processing.
Findings. The developed three-dimensional post stack full-wave finite-difference migration with parallelization of computing process for processing has been tested in a model and real mode. The obtained results confirm the applicability of the developed method of migration in studding the geological environment of deep structure with different degrees of complexity. To demonstrate the effectiveness of this method we compared the results obtained with those obtained using standard software migration system ProMAX and the developed program with parallelization of computing process on the cluster, developed at the Institute of Geophysics. The comparison of the results allows us to emphasize a general similarity of the results and the difference in some of the particular parts of the image (larger extension of reflecting horizons in the direction of the salt body as a result of applying the proposed variant of post stack full-wave finite-difference migration), which may be attributed to a more accurate migration transformation in the developed program.
Practical value/implications. The developed version of a three-dimensional post stack full-wave finite-difference migration with parallelization of computing process allows on to carry out high-quality processing of large volumes of spatial seismic data in a short time, which depend on the number of processors in the cluster. The results of the testing of developed programs as in model and real data areal seismic survey, prove accuracy and efficiency even in the structure of the medium complicated by the presence of salt body, which is important for oil and gas companies,
exploration activities.